Kecerdasan Budaya Guru BK dan Implikasinya pada Layanan Konseling Multikultural - Laily Tiarani Soejanto; Khairul Bariyyah; Santy Andrianie (Jurnal Psikoedukasi dan Konseling, 2025)
Cultural intelligence is essential for school counselors to provide effective multicultural counseling. This study examines the cultural intelligence levels of guidance and counseling teachers in East Java, Indonesia, focusing on its four dimensions: metacognitive, cognitive, motivational, and behavioral. The research aims to assess their ability to address diverse student needs in multicultural contexts. Using a survey method, data were collected from 328 school counselors through the Cultural Intelligence Scale, comprising 20 items. Descriptive analysis categorized participants' cultural intelligence levels and identified strengths and areas needing improvement. Results showed that 66.70% of participants had high cultural intelligence, 33% moderate, and 0.30% low. Most counselors excelled in motivational and behavioral dimensions, demonstrating strong adaptability and willingness to engage with cultural diversity. However, variability in the cognitive dimension suggests a need for further development in cultural understanding. This study concludes that cultural intelligence is a vital competency for inclusive and adaptive counseling services. Targeted training programs are recommended to address gaps, particularly in cognitive skills, to enhance counselors' effectiveness in multicultural settings. These findings provide valuable insights for developing strategies to strengthen cultural competencies in educational counseling practices, ensuring services meet the diverse needs of students.